Sovereign Debt Crisis in Portugal and Spain - António Afonso; Nuno Verdial (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2020)
The 2007-2008 financial crisis and the European sovereign debt crisis effects rippled through the financial system, banks and sovereign states. We analyze these events, focusing on the Portuguese and Spanish case after providing an insight into the Eurozone. We assessed the pricing of sovereign risk by performing an OLS/2SLS fixed effects panel analysis on a pool of Eurozone countries and a SUR regression with Portugal and Spain covering the period 1999:11 until 2019:6. Our results show that the pricing of sovereign risk changed with the crisis and the "whatever it takes" speech of Mario Draghi. Specifically, market pricing of the Eurozone credit risk, liquidity risk and the risk appetite increased after the crisis and it relaxed afterwards. We did not find evidence of specific pricing regime changes after the speech in the Portuguese and Spanish case.
Keywords: C23; E44; E52; G01; 330; Sovereign debt; Yield spreads; Crises; Unconventional Monetary Policy; Portugal; Spain